La peur, l’angoisse et la violence domestique dans Cendres et braises de Ken Bugul - Swoboda, Anna (Romanica Silesiana)
The autobiographical novel Cendres et braises by Ken Bugul, a contemporary Senegalese author, presents a comprehensive overview of the victim’s behavior in a violent relationship. By using strong defense mechanisms, the abused woman becomes emotionally attached to her aggressor, isolates herself, refuses any help and stays trapped in the cycle of violence. In the case of Marie, the novel’s main character, anxiety has always been the basis of her relationships since she was abandoned by her mother. The purpose of this study is to analyze the dynamics between the victim and the abuser, as well as to show that anxiety is the source of self-destructive behavior and examine how it keeps the woman in an abusive relationship. Key words: fear, violence, relationship, woman, abuse